Removal of Cd2+ from Artificial Waste Using Natural Zeolite: Study on Adsorption Equilibrium - Nainggolan, Ekelesia Martina; Mulyono, Panut; Prasetya, Agus (2022)
This study reports the removal of cadmium ions in an aqueous solution as the artificial waste using natural zeolite as the adsorbent. Natural zeolite was characterized by using XRD (X-ray Diffraction) and XRF (X-ray fluorescence) analysis. The XRD results show that the natural zeolite derived from Klaten, Jawa Tengah, is mordenite type, and the XRF results show that Si/Al ratio is 5.69 (medium). A batch adsorption method is carried out at room temperature varied adsorbent dose. Equilibrium of adsorption data was analyzed using the Langmuir and Freundlich isotherm model. The values of the parameters constants for the Langmuir equation were qmax =-2.301 mg/g and KL =-1.00067 while the Freundlich equation were Kf = 3.999 and n = 0.845. It was found that the Freundlich adsorption model is better than the Langmuir isotherm model with a high coefficient of determination. In this study, the removal efficiency for Cd2+ was 99.4 for an adsorbent dose of 70 g/L. It can be concluded that the natural zeolite of mordenite type is a very potential adsorbent for the removal of Cd2+ . Therefore, the utilization of zeolite should be encouraged on a larger scale, especially in environmental applications. © 2022 Trans Tech Publications Ltd, Switzerland